1989
DOI: 10.1002/anr.1780320216
|View full text |Cite
|
Sign up to set email alerts
|

Home central venous hyperalimentation in fifteen patients with severe scleroderma bowel disease

Abstract: Fifteen patients with severe scleroderma bowel disease began receiving home central venous hyperalimentation (HCVH) between 1979 and 1987. The major reasons for instituting HCVH were intestinal pseudoobstruction, malabsorption, and malnutrition. Eleven patients had an improved quality of life. Serious complications encountered over these 15,700 catheter-use days were 2 episodes of septicemia and 2 episodes of superior vena cava obstruction. Seven patients died, but none directly from their gastrointestinal dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…20,31e33,36,40e42 Patients with systemic sclerosis (SSc) had the poorest outcome of 57% survival at 3 years. 46 20,23,31e33,37,41,42 or radiation enteritis, 20,23,31,32,37,41e45 with approximately 60% surviving at 5 years. The survival rate of patients with intra-abdominal desmoids in familial polyposis depends on the stage of the tumor; the 10-year survival for mild, moderate, or severe stage disease, was 95%, 85% and 65%, respectively.…”
Section: Weaning From Hpn After Intestinal Rehabilitationmentioning
confidence: 99%
“…20,31e33,36,40e42 Patients with systemic sclerosis (SSc) had the poorest outcome of 57% survival at 3 years. 46 20,23,31e33,37,41,42 or radiation enteritis, 20,23,31,32,37,41e45 with approximately 60% surviving at 5 years. The survival rate of patients with intra-abdominal desmoids in familial polyposis depends on the stage of the tumor; the 10-year survival for mild, moderate, or severe stage disease, was 95%, 85% and 65%, respectively.…”
Section: Weaning From Hpn After Intestinal Rehabilitationmentioning
confidence: 99%
“…HRQOL has been assessed in several other chronic GID such as patients with short bowel symdrome receiving home parenteral nutrition (HPN),9 113 114 and those with gastroparesis,115 116 achalasia,117 and chronic intestinal bleeding,118 and appears to be impaired in all of these disorders. Patients receiving HPN had significantly worse IBDQ scores (mean 5.0 v 5.6, respectively; p<0.05) and SIP scores (mean 17% v 8%, respectively (higher scores worse); p<0.001) than patients with short bowel who were not receiving HPN.…”
Section: Other Gastrointestinal Conditionsmentioning
confidence: 99%
“…The 2 other studies retrospectively analyzed cases that prescribed home parenteral nutrition . Quality scores show that the most recent study has a low risk of bias, though the other had poorly reported outcomes .…”
Section: Resultsmentioning
confidence: 99%